2020
DOI: 10.3390/ijms21020606
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Promotes Motor Function after Experimental Stroke and Enhances Recovery-Promoting Mechanisms within the Peri-Infarct Area

Abstract: Motor impairment is the most common and widely recognised clinical outcome after stroke. Current clinical practice in stroke rehabilitation focuses mainly on physical therapy, with no pharmacological intervention approved to facilitate functional recovery. Several studies have documented positive effects of growth hormone (GH) on cognitive function after stroke, but surprisingly, the effects on motor function remain unclear. In this study, photothrombotic occlusion targeting the motor and sensory cortex was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 100 publications
0
38
0
1
Order By: Relevance
“…However, we only investigated the neurorestorative effects of GH treatment within the peri-infarct regions [ 24 ]. The observed enhancement of recovery-promoting mechanisms within the peri-infarct area is most likely contributing to the improvement in motor outcomes [ 25 ], whereas the promotion of hippocampal neurogenesis and increased synaptic plasticity reported here are likely to be of importance for improved cognition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we only investigated the neurorestorative effects of GH treatment within the peri-infarct regions [ 24 ]. The observed enhancement of recovery-promoting mechanisms within the peri-infarct area is most likely contributing to the improvement in motor outcomes [ 25 ], whereas the promotion of hippocampal neurogenesis and increased synaptic plasticity reported here are likely to be of importance for improved cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we explored the effect of GH treatment on cerebrovascular remodeling. In our previous studies, we showed that GH has the ability to enhance angiogenesis, and increases the density and area coverage of both CD31 and Collagen IV–positive cells in the peri-infarct region [ 24 , 25 ]. In the current study, we analyzed vessel density in the hippocampus area using immunofluorescence labelled tomato lectin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations